2013
DOI: 10.1161/strokeaha.113.002936
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Trends in Long-Term Mortality Risk in 17 149 Survivors of Ischemic Stroke Less Than 55 Years of Age

Abstract: Background and Purpose-The purpose of the present study was to investigate the 4-year mortality risk among patients <55 years with a first ischemic stroke during 1987-2006. Methods-A total of 17 149 cases (37.4% women) aged 18 to 54 years who survived ≥28 days after a first ischemic stroke were identified in the Swedish Inpatient Register from 1987 to 2006. All patients were followed for 4 years or until death. The standardized mortality ratio was calculated by comparing the mortality rates with those of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
3
24
0
1
Order By: Relevance
“…In another recent registry-based study from Sweden, the SMR for all patients with ischemic stroke aged 18 to 54 years was 8.15, which is in line with our figures considering the different age cuf off. 7 The average annual mortality rate in our study (1.6%) was in accordance with previous studies (1.4%-1.6%). 4,28 In our study, factors associated with mortality during the follow-up are similar to previous ones because our analysis showed that increasing age, active malignancy, type 1 diabetes mellitus, heart failure, heavy drinking, stroke in multiple territories, and increasing NIHSS score are associated with long-term mortality at young age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In another recent registry-based study from Sweden, the SMR for all patients with ischemic stroke aged 18 to 54 years was 8.15, which is in line with our figures considering the different age cuf off. 7 The average annual mortality rate in our study (1.6%) was in accordance with previous studies (1.4%-1.6%). 4,28 In our study, factors associated with mortality during the follow-up are similar to previous ones because our analysis showed that increasing age, active malignancy, type 1 diabetes mellitus, heart failure, heavy drinking, stroke in multiple territories, and increasing NIHSS score are associated with long-term mortality at young age.…”
Section: Discussionsupporting
confidence: 93%
“…If no visible ischemic lesion was present but symptoms lasted for 24 hours, lesion size was considered small. 18 Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) both as a total score at admission and as divided into mild (0-6), moderate (7)(8)(9)(10)(11)(12)(13)(14), and severe (≥15). 19 The classification of stroke pathogenesis was done independently by pairs of investigators, reaching consensus when necessary.…”
Section: Baseline Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cardiovascular diseases were shown to be most common causes of death among younger ischemic stroke survivors (Giang et al. 2013). During the first decade of our investigation (1983–2003), a statistically valid decrease in body mass index in Lithuanian men was observed (Nichols et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors propose a hypothesis that the progressive male hormones (testosterone) deficiency is a major cause of difference in survival between the sexes in patients with stroke (Giang et al. 2013). Moreover, our study found that male standardized mortality rate during the study period decreased by 35% and that of females by 63%.…”
Section: Discussionmentioning
confidence: 99%